Genomic Profiling of Intrahepatic Cholangiocarcinoma: Refining Prognosis and Identifying Therapeutic Targets - Zhu, Andrew X.; Borger, Darrell R.; Kim, Yuhree; Cosgrove, David; Ejaz, Aslam; Alexandrescu, Sorin; Groeschl, Ryan Thomas; Deshpande, Vikram; Lindberg, James M.; Ferrone, Cristina; Sempoux, Christine; Yau, Thomas; et al. (Annals of surgical oncology, 2014)
Background The molecular alterations that drive tumorigenesis in intrahepatic cholangiocarcinoma (ICC) remain poorly defined. We sought to determine the incidence and prognostic significance of mutations associated with ICC among patients undergoing surgical resection. Methods Multiplexed mutational profiling was performed using nucleic acids that were extracted from 200 resected ICC tumor specimens from 7 centers. The frequency of mutations was ascertained and the effect on outcome was determined. Results The majority of patients (61.5 %) had no genetic mutation identified. Among the 77 patients (38.5 %) with a genetic mutation, only a small number of gene mutations were identified with a frequency of >5 %: IDH1 (15.5 %) and KRAS (8.6 %). Other genetic mutations were identified in very low frequency: BRAF (4.9 %), IDH2 (4.5 %), PIK3CA (4.3 %), NRAS (3.1 %), TP53 (2.5 %), MAP2K1 (1.9 %), CTNNB1 (0.6 %), and PTEN (0.6 %). Among patients with an IDH1 -mutant tumor, approximately 7 % were associated with a concurrent PIK3CA gene mutation or a mutation in MAP2K1 (4 %). No concurrent mutations in IDH1 and KRAS were noted. Compared with ICC tumors that had no identified mutation, IDH1 -mutant tumors were more often bilateral (odds ratio 2.75), while KRAS -mutant tumors were more likely to be associated with R1 margin (odds ratio 6.51) (both P < 0.05). Although clinicopathological features such as tumor number and nodal status were associated with survival, no specific mutation was associated with prognosis. Conclusions Most somatic mutations in resected ICC tissue are found at low frequency, supporting a need for broad-based mutational profiling in these patients. IDH1 and KRAS were the most common mutations noted. Although certain mutations were associated with ICC clinicopathological features, mutational status did not seemingly affect long-term prognosis.